Legal Protection For E-Commerce Businesses Against Consumer Reviews - Julia Choeirunnissa; Martin Situmorang; Muhamad Zidan; Endang Sutrisno; Alip Rahman (Journal Of Social Science (JoSS), 2024)
In e-commerce, customer reviews play an important role in influencing the decisions made by customers. Before making a purchase, many people read positive customer reviews because they can offer useful information to potential buyers and increase their overall level of trust in the product. Positive customer reviews also help a store look more credible However, what happens to business actors is not as expected, so consumers act in bad faith by making bad judgments in marketplace product reviews. The purpose of this study is to analyze the good faith of business actors and how it impacts the law established by the Consumer Protection Law. This study uses a normative legal research study whose findings show that consumers are not liable for criticism that harms business entities, in accordance with the Consumer Protection Law (UUPK). In particular, Article 5a requires consumers to pay special attention to product descriptions listed in stores.